Complement Receptor 3-Mediated Inhibition of Inflammasome Priming by Ras GTPase-Activating Protein During Francisella tularensis Phagocytosis by Human Mononuclear Phagocytes - Hoang, Ky V.; Rajaram, Murugesan V. S.; Curry, Heather Marie; Gavrilin, Mikhail A.; Wewers, Mark D.; Schlesinger, Larry S. (Frontiers in Immunology, 2018)
Francisella tularensis is a remarkably infectious facultative intracellular bacterium of macrophages that causes tularemia. Early evasion of host immune responses contributes to the success of F. tularensis as a pathogen. F. tularensis entry into human monocytes and macrophages is mediated by the major phagocytic receptor, Complement Receptor 3 (CR3, CD11b/CD18). We recently determined that despite a significant increase in macrophage uptake following C3 opsonization of the virulent Type A F. tularensis spp. tularensis Schu S4, this phagocytic pathway results in limited pro-inflammatory cytokine production. Notably, MAPK/ERK activation is suppressed immediately during C3-opsonized Schu S4-CR3 phagocytosis. A mathematical model of CR3-TLR2 crosstalk predicted early involvement of Ras GTPase Activating Protein (RasGAP) in immune suppression by CR3. Here we link CR3-mediated uptake of opsonized Schu S4 by human monocytes and macrophages with inhibition of early signal 1 inflammasome activation, evidenced by limited caspase-1 cleavage and IL-18 release. This inhibition is due to increased RasGAP activity, leading to a reduction in the Ras-ERK signaling cascade upstream of the early inflammasome activation event. Thus, our data uncover a novel signaling pathway mediated by CR3 following engagement of opsonized virulent F. tularensis to limit inflammasome activation in human phagocytic cells, thereby contributing to evasion of the host innate immune system.